Cardiopulmonary Function and Aerobic Exercise in Parkinson's: A Systematic Review of the Literature. Issue 6 (25th July 2020) - Aburub, Aseel; Ledger, Sean J.; Sim, Julius; Hunter, Susan M.
ABSTRACT: Background: Cardiorespiratory impairments are considered the main cause of mortality in the late stages of Parkinson's. Aerobic exercise has been shown to improve pulmonary function in asthmatic patients and in healthy people. However, effects of aerobic exercise on cardiopulmonary function in people with Parkinson's have not been investigated. Therefore, this study aimed to review the effects of aerobic exercise on cardiopulmonary function in people with Parkinson's. Methods: A systematic search was conducted using MEDLINE, AMED, CINHAL Plus, and relevant associated keywords, from January 1970 to January 2020. Inclusion criteria for the studies were: aerobic exercise as part of the intervention, pulmonary function test, and/or cardiopulmonary exercise test as outcome measures. Results: In total, 329 citations were identified from the search, of which nine were included in this review. In general, aerobic exercise was found to have positive effects on cardiac function for people with Parkinson's, but there is a lack of studies on the effects of aerobic exercise on pulmonary function. Conclusion: People with early stages of Parkinson's may experience positive effects of aerobic exercise on cardiac fitness. Further research is needed in this area, particularly into the effects of aerobic exercise on pulmonary function in early stages of the disease.